2020
DOI: 10.1098/rsta.2019.0186
|View full text |Cite
|
Sign up to set email alerts
|

Organic semiconductors for visible light communications

Abstract: Organic semiconductors are an important class of optoelectronic material that are widely studied because of the scope for tuning their properties by tuning their chemical structure, and simple fabrication to make flexible films and devices. Although most effort has focused on developing displays and lighting from these materials, their distinctive properties also make them of interest for visible light communications (VLCs). This article explains how their properties make them suitable for VLC and revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 95 publications
(134 reference statements)
0
32
0
2
Order By: Relevance
“…While it has been shown that it is possible to achieve gigabit per second links using organic LEDs (OLEDs) [13], it has also been demonstrated that organic photovoltaic cells can be used as high-speed data detectors. This issue includes a review article by Samuel and co-workers [14], who have been leading the development of record achieving organic VLC devices.…”
Section: (A) Devices and Componentsmentioning
confidence: 99%
“…While it has been shown that it is possible to achieve gigabit per second links using organic LEDs (OLEDs) [13], it has also been demonstrated that organic photovoltaic cells can be used as high-speed data detectors. This issue includes a review article by Samuel and co-workers [14], who have been leading the development of record achieving organic VLC devices.…”
Section: (A) Devices and Componentsmentioning
confidence: 99%
“…So far, over 1300 species of LMOFs have been reported, from which much feasibility still hold up to be studied as phosphors for the approaching luminescent devices [84]. The large amount of LMOFs and their hybrid materials have been developed in the recent past as potential candidates for OLEDs application [85][86][87].…”
Section: The Harnessing Of Mofs and Their Hybrid Materialsmentioning
confidence: 99%
“…The diffused LED beam, however, leads to lower signal strength, and thus relatively shorter achievable distance and data rate [76]. Recent research efforts aim to increase the data rate of LEDs recent studies show that Organic LEDs (OLEDs) can help achieve high data rates up to 1.13 Gbps [77]. Another study by Tsonev et al demonstrates a 3 Gbps FSO link utilizing a single 50-µm gallium nitride LED and Orthogonal frequency division multiplexing (OFDM) modulation scheme [78].…”
Section: B Transmittersmentioning
confidence: 99%